MEMBANGUN KREATIVITAS MELALUI PEMBELAJARAN SENI TARI DAN ANALISIS KURIKULUM DI SANGGAR TARI KRANS SITUBONDO - Cristina Handayani; Indar Sabri; Welly Suryandoko; Warih Handayaningrum; Martadi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Non-formal education is important as a complement to formal education, in order to support, strengthen and develop the learning process. In the implementation of education both formal and formal education in the implementation of learning cannot be separated from the curriculum to achieve educational goals. One of the non-formal education is dance studio. Krans Dance Studio is a dance studio located in Situbondo. The purpose of this study is to describe and analyze more deeply the planning and implementation of the dance learning curriculum at Krans Dance Studio. The method used in this research is descriptive qualitative with data collection of observation, interviews, and documentation. The data were analyzed by reducing, presenting data, and drawing conclusions. The conclusion of this research shows that non-formal education, especially in dance learning at Krans Dance Studio Situbondo, plays an important role in developing creativity, preserving local culture, and shaping the character of students. Dance learning in this studio combines dance techniques with exploration of cultural values, which builds students' expressive abilities and innovation. The curriculum implemented is designed to balance the teaching of traditional arts with the times, using structured methods and periodic evaluations. Overall, Krans Dance Studio has succeeded in creating a space that supports the development of young people's creative skills and the preservation of traditional dance.